Scenarios for Strategic Conversation with Parents in the Malaysian After-School Market-Education Sector - Hua Loon, Ling (2007)
A key challenge for the Malaysian after-school market-education sector organisations has been to communicate with parents to involve them beyond them being mere customers or bystanders in their children’s education. This dissertation is designed to move towards a new model for operation. Review of the literature led to the exploration of scenario stories as a tool for strategic conversation with parents to explore perception and guide choice in education. Scenario plots for the Malaysian education sector were written and used in a self-completion questionnaire survey. 61 individuals (parents, educators and other adults) participated and, from their responses, scenario end-states for the Malaysian national schools and the Malaysian after-school market-education sector were developed. The use of scenarios in this way was generally found to be helpful by the parents. Examining scenarios for both parent and organisation learning, a learning framework was devised with two levels of change: a shallow learning change to the behaviour, and a deeper learning change to the underlying values that drive the behaviour. Scenarios provide the perspective needed to determine the appropriate level of adaptation needed. I hope to utilise this framework with the stakeholders in my future work as I start my own private afterschool education organisation.